Globalization hazard and delayed reform in emerging markets - Calvo, Guillermo A. (2002)
This paper focuses on capital flow volatility in Emerging Market Economies, EMs. Capital inflows rose to unprecedented heights in the first part of the 1990s, and collapsed very rapidly in the second. Volatility could partly be explained by financial vulnerability in the EMs themselves, but the global nature of the phenomenon raises the suspicion that there are systemic problems largely independent of each individual country. The paper puts forward the conjecture that phenomena like contagion could stem from the way the capital market operates (e.g., crises generated by “margin calls”). These systemic phenomena require systemic instruments. Unfortunately, few are available. The IMF is more a Fire Department than a Central Bank. Liquidity is sprayed where fire is found, not on the whole system like a Central Bank does when there is a liquidity crisis.